Polycrystalline phase SnSe / NiSe / Ni3Se2 hybrid nanorod array material as well as preparation method and application thereof

By using the polycrystalline SnSe/NiSe/Ni3Se2 hybrid nanorod array material as an electrocatalyst, the problems of slow kinetics and high overpotential in the urea oxidation reaction are solved, and efficient catalysis in the electrolytic water hydrogen production is achieved, especially in the It exhibits excellent electrocatalytic activity and long-term stability at high current density.

CN119465269AActive Publication Date: 2025-02-18NANJING NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411623771.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

In the prior art, urea oxidation reaction (UOR) seriously restricts the efficiency of electrolyzing hydrogen production due to its slow kinetics and high overpotential potential, and the activity and stability of traditional catalysts are insufficient.

Method used

The polycrystalline phase SnSe/NiSe/Ni3Se2 hybrid nanorod array material was used as an electrocatalyst. The material was prepared by a one-step hydrothermal reaction method, and its novel multiphase hybrid structure design was used to improve the catalytic performance.

Benefits of technology

In the electrolytic water hydrogen production assisted by urea oxidation reaction, hydrogen evolution reaction and urea oxidation reaction, the polycrystalline SnSe/NiSe/Ni3Se2 hybrid nanorod array material exhibits excellent catalytic performance, including excellent electrocatalytic activity under high current density and long-term stability, significantly reduces energy consumption and extends the stability of the electrocatalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465269A_ABST
    Figure CN119465269A_ABST
Patent Text Reader

Abstract

The invention discloses a polycrystalline phase SnSe / NiSe / Ni3Se2 hybrid nanorod array material as well as a preparation method and application of the polycrystalline phase SnSe / NiSe / Ni3Se2 hybrid nanorod array material. According to the method, Se powder is reduced into a transparent solution through NaBH4 in an N2 saturated atmosphere, then a mixed solution of SnCl2. 2H2O and NaOH, an NH4F solution and foamed nickel are added, and the polycrystalline phase SnSe / NiSe / Ni3Se2 hybrid nanorod array electrocatalyst growing on a foamed nickel framework in situ can be obtained through a high-temperature hydrothermal reaction. The preparation process is simple and environment-friendly, the raw materials are easy to obtain, the synthesis controllability is high, and the product repeatability is good. The prepared advanced polycrystalline phase SnSe / NiSe / Ni3Se2 hybrid nanorod array has a specific active component and a uniform morphology structure, and is easy to prepare at high throughput. Meanwhile, the uniform nanorod array structure has a large specific surface area, can provide more reaction active sites, shows excellent electrocatalytic urea oxidation reaction, hydrogen evolution reaction and urea oxidation reaction assisted water electrolysis catalytic performance, and provides important assistance for the development of the field of efficient and energy-saving hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polycrystalline SnSe / NiSe / Ni 3 Se 2 The invention relates to a hybrid nanorod array material and a preparation method and application thereof, belonging to the field of nanomaterials and their preparation and application catalysis. Background Art

[0002] In the context of global energy structure transformation, hydrogen energy is regarded as an important carrier for promoting rapid transformation of energy structure and achieving environmental protection due to its advantages such as clean, efficient and renewable. At present, the traditional methane steam reforming hydrogen production technology is heavily dependent on fossil fuels, which not only releases a large amount of carbon dioxide but also cannot guarantee sustainable production. In contrast, water electrolysis hydrogen production has significant advantages such as abundant raw materials, low carbon emissions and environmental friendliness. The entire process of water electrolysis consists of two half reactions, namely hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Among them, the OER reaction seriously restricts the efficiency of hydrogen production due to its slow kinetics and high overpotential barrier. Therefore, finding an advanced reaction to replace OER is of great significance for promoting the progress of hydrogen production technology. Recently, urea oxidation reaction (UOR) has attracted much attention due to its low theoretical thermodynamic potential (0.37V). Replacing OER with it in the hydrogen production process can achieve significant reduction in energy consumption and efficient energy conversion. In particular, urea is widely present in industrial wastewater. Through UOR, not only can the effective treatment of wastewater be achieved, but also urea can be converted into energy, thus achieving the dual benefits of wastewater treatment and energy production. Furthermore, from the perspective of screening the active components of the catalyst, nickel selenide has a unique Ni 2+ (t 2g 6 e g 2 ) electronic structure, which enables it to exhibit excellent electrocatalytic UOR activity, but its related catalytic activity and operational stability still need to be further improved.

[0003] Polycrystalline hybrid design can not only inherit the unique catalytic properties of different components, but also synergistically build multiple active centers. In particular, polycrystalline hybrid interfaces tend to create more high-energy active sites and more compatible electron density, which provides more possibilities for optimizing the electronic structure of the interface and significantly improving the catalytic performance. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a polycrystalline SnSe / NiSe / Ni 3 Se 2Hybrid nanorod array material and its preparation method and application. The preparation method is simple to operate, the reaction conditions are controllable, and the repeatability is strong. The obtained material is a polycrystalline SnSe / NiSe / Ni with an in-situ grown nickel foam skeleton. 3 Se 2 Hybrid nanorod array material. SnSe / NiSe / Ni 3 Se 2 Hybrid nanorod arrays have good application prospects in urea oxidation reaction, hydrogen evolution reaction and hydrogen production from water electrolysis assisted by urea oxidation reaction.

[0005] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0006] A polycrystalline SnSe / NiSe / Ni 3 Se 2 The preparation method of hybrid nanorod array material comprises the following steps:

[0007] (1) While continuously feeding N 2 In an atmosphere of 4 Completely dissolve in deionized water, then add Se powder until it is reduced to a clear and transparent solution;

[0008] (2) Add SnCl to the clear solution in step (1) in sequence 2 ·2H 2 O and NaOH mixed solution, NH 4 F solution and nickel foam, followed by hydrothermal reaction, and finally obtaining the polycrystalline SnSe / NiSe / Ni in situ vertically grown on the nickel foam skeleton. 3 Se 2 Hybrid nanorods.

[0009] As an improvement, the NaBH 4 The amount of substance is 1~6mmol, the amount of Se powder is 1~4mmol, and the volume of deionized water is 1~6mL.

[0010] As an improvement, the SnCl 2 ·2H 2 The amount of O is 0.05mmoL, the amount of NaOH is 0.5-1.5mmoL, and the amount of NH 4 The amount of F is 1-2 mmoL, the SnCl 2 ·2H 2 The volume of the mixed solution of O and NaOH is 1 mL, NH 4 The volume of solution F is 25 mL.

[0011] As an improvement, the temperature of the hydrothermal reaction in step (2) is 120-200° C., and the reaction time is 4-12 h.

[0012] As an improvement, the area of ​​the nickel foam described in step (2) ranges from 1×2 to 2×4 cm 2 .

[0013] The polycrystalline SnSe / NiSe / Ni prepared by the above preparation method 3 Se 2 Hybrid nanorod array material, composed of orthorhombic SnSe, hexagonal NiSe and rhombohedral Ni 3 Se 2 Composed of SnSe / NiSe / Ni 3 Se 2 The diameter of the hybrid nanorods is 100 to 300 nm.

[0014] Any of the above polycrystalline SnSe / NiSe / Ni 3 Se 2 Application of hybrid nanorod array materials as electrocatalysts in urea oxidation reaction, hydrogen evolution reaction and hydrogen production from water electrolysis assisted by urea oxidation reaction.

[0015] As an improvement, when the urea oxidation reaction is assisted by water electrolysis to produce hydrogen, SnSe / NiSe / Ni 3 Se 2 ||SnSe / NiSe / Ni 3 Se 2 Electrolyzer, at 1.37V and 1.54V, achieved a driving current of 10mA cm -2 and 100mA cm -2 .

[0016] Beneficial effects:

[0017] Compared with the prior art, the present invention provides a polycrystalline SnSe / NiSe / Ni 3 Se 2 Hybrid nanorod array materials and their preparation methods and applications have the following advantages:

[0018] 1. The present invention prepares advanced polycrystalline SnSe / NiSe / Ni by a one-step hydrothermal reaction method. 3 Se 2 Hybrid nanorod array material with advanced orthorhombic SnSe, hexagonal NiSe and rhombohedral Ni 3 Se 2 It has a polycrystalline structure, and its synthesis process is simple and environmentally friendly, the raw materials are easy to obtain, the synthesis is highly controllable, and the product is reproducible.

[0019] 2. Polycrystalline SnSe / NiSe / Ni prepared by the present invention 3 Se 2 The hybrid nanorod array material has excellent catalytic performance at high current density in HER, UOR and UOR-assisted water electrolysis hydrogen production reactions. For HER, it has excellent catalytic performance at 10, 100 and 500 mA cm -2 The overpotentials at the current densities are 116mV, 237mV, and 311mV, respectively, and the Tafel slope is 39mV dec -1 For UOR, the -2 The voltages at the current density are 1.31V, 1.39V, and 1.44V, respectively, and the Tafel slope is 31mV dec -1 . Further assembled SnSe / NiSe / Ni 3 Se 2 ||SnSe / NiSe / Ni 3 Se 2 The electrolyzer only needs 1.41V and 1.61V to drive 10 and 100mA cm -2 The excellent bifunctional electrocatalytic activity is mainly due to the promotion of the novel multiphase hybrid structure design, which significantly improves the kinetics of the catalytic reaction. In particular, its excellent electrocatalytic performance at high current density is expected to be further expanded to commercial applications.

[0020] 3. In addition to using the polycrystalline hybridization strategy to adjust the microstructure of the electrocatalyst, the present invention also uses local near-infrared light (NIR) irradiation on the catalyst surface to integrate the photothermal effect into the electrocatalytic reaction process, synergistically improving the thermodynamics of the reaction and the interfacial electron transfer rate, and improving mass transfer. For UOR, polycrystalline SnSe / NiSe / Ni 3 Se 2 The hybrid nanorods only require 1.28 V, 1.34 V, and 1.37 V to achieve 10, 500, and 1000 mA cm -2 , Tafel slope is 22mVdec -1 . Further assembled SnSe / NiSe / Ni 3 Se 2 ||SnSe / NiSe / Ni 3 Se 2 The electrolyzer only needs 1.37V and 1.54V to drive 10 and 100mA cm -2In addition, this local NIR light heating method can also suppress the rise of the temperature of the entire electrolyte, which not only significantly reduces energy consumption, but also prolongs the stability of the electrocatalyst in long-term cycle tests, making SnSe / NiSe / Ni 3 Se 2 ||SnSe / NiSe / Ni 3 Se 2 The electrolyzer can be operated at 100 mA cm -2 It can run stably for 120 hours at a current density of 10 ... BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 SEM image of hybrid nanorod array material;

[0022] Figure 2 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 XRD pattern of hybrid nanorod array material;

[0023] Figure 3 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 HRTEM image of the hybrid nanorod array material (a) and a further magnified HRTEM image (b) of the corresponding area in (a);

[0024] Figure 4 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 HADDF-STEM image of hybrid nanorod array material;

[0025] Figure 5 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 Mapping diagram of hybrid nanorod array material;

[0026] Figure 6 The polycrystalline SnSe / NiSe / Ni prepared in Example 2 of the present invention 3 Se 2 SEM image of hybrid nanorod array material;

[0027] Figure 7 The polycrystalline SnSe / NiSe / Ni prepared in Example 3 of the present invention 3 Se2 SEM image of hybrid nanorod array material;

[0028] Figure 8 The rhombohedral NiSe / Ni prepared in Comparative Example 1 of the present invention 3 Se 2 SEM image of hybrid nanorod array material;

[0029] Fig. 9 The rhombohedral NiSe / Ni prepared in Comparative Example 1 of the present invention 3 Se 2 XRD pattern of hybrid nanorod array material;

[0030] Fig.10 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 Hybrid nanorod array material and rhombohedral NiSe / Ni prepared in Comparative Example 1 3 Se 2 LSV polarization curves of HER (a) and UOR (b) of hybrid nanorod array materials;

[0031] Fig.11 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 Hybrid nanorod array material and rhombohedral NiSe / Ni prepared in Comparative Example 1 3 Se 2 HER Tafel slope (a) and UOR Tafel slope (b) of hybrid nanorod array materials;

[0032] Fig.12 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 UOR LSV polarization curve of hybrid nanorod array material under NIR near-infrared light;

[0033] Fig.13 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 The performance of water electrolysis to produce hydrogen assisted by urea oxidation reaction assembled from hybrid nanorod array materials;

[0034] Fig.14 The polycrystalline SnSe / NiSe / Ni prepared in Example 1 of the present invention 3 Se 2 Stability test of the urea oxidation reaction-assisted water electrolysis hydrogen production electrolyzer assembled with hybrid nanorod array materials. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described in detail below through specific embodiments. However, it is necessary to point out that the following embodiments are only used to describe the content of the invention and do not constitute a limitation on the protection scope of the present invention.

[0036] Example 1 Polycrystalline SnSe / NiSe / Ni 3 Se 2 Preparation of hybrid nanorod array materials

[0037] (1) While continuously feeding N 2 Under the atmosphere of 4 Completely dissolve in 3 mL of deionized water, then add 1 mmol of Se powder until it is reduced to a clear and transparent solution.

[0038] (2) Add 0.05 mmol SnCl 2 ·2H 2 O and a mixed solution of 0.5 mmol NaOH (volume 1 mL), 1.5 mmol NH 4 F solution (volume 25 mL) and an area of ​​1 × 4 cm 2 The nickel foam was then hydrothermally reacted at 180 °C for 12 h to finally obtain the polycrystalline SnSe / NiSe / Ni 3 Se 2 Hybrid nanorod array materials.

[0039] The polycrystalline SnSe / NiSe / Ni prepared in Example 1 3 Se 2 Hybrid nanorod array materials were analyzed by scanning electron microscopy. Figure 1 As shown, the prepared polycrystalline SnSe / NiSe / Ni 3 Se 2 The nanorod arrays grow uniformly and vertically on the nickel foam skeleton and there are gaps between the rods.

[0040] The polycrystalline SnSe / NiSe / Ni prepared in Example 1 3 Se 2 Hybrid nanorod array materials were subjected to XRD analysis. Figure 2 As shown, its characteristic peaks are similar to those of orthorhombic SnSe (standard card JCPDS 48-1224), hexagonal NiSe (standard card JCPDS75-0610) and rhombohedral Ni 3 Se 2(Standard card JCPDS19-0841) The three standard cards match well, indicating the successful preparation of the polycrystalline phase structure. At the same time, the HRTEM image further shows the SnSe / NiSe / Ni 3 Se 2 The multiphase structure, such as Figure 3 As shown in the figure, the lattice spacings of 0.27 nm, 0.21 nm, and 0.29 nm correspond to the (101) crystal plane of the hexagonal NiSe, the (101) crystal plane of the rhombohedral NiSe, respectively. 3 Se 2 The (202) crystal plane of SnSe and the (111) crystal plane of orthorhombic SnSe are consistent with the XRD results.

[0041] The polycrystalline SnSe / NiSe / Ni prepared in Example 1 3 Se 2 The hybrid nanorod array material was analyzed by HADDF-STEM and element mapping. Figure 4 (HADDF-STEM image) and Figure 5 (Element mapping analysis) shows that the three elements Ni, Se and Sn are evenly distributed in the nanorods.

[0042] Example 2 Polycrystalline SnSe / NiSe / Ni 3 Se 2 Preparation of hybrid nanorod array materials

[0043] Except that the amount of NaOH in step (2) is 1.0 mmoL, the rest is the same as in Example 1.

[0044] The polycrystalline SnSe / NiSe / Ni prepared in Example 2 3 Se 2 Hybrid nanorod array materials were analyzed by scanning electron microscopy. Figure 6 As shown, the prepared polycrystalline SnSe / NiSe / Ni 3 Se 2 The nanorod arrays grow uniformly and vertically on the nickel foam skeleton and there are gaps between the rods.

[0045] Example 3 Polycrystalline SnSe / NiSe / Ni 3 Se 2 Preparation of hybrid nanorod array materials

[0046] Except that the amount of NaOH substance in step (2) is 1.5 mmol / L, the rest is the same as Example 1.

[0047] The polycrystalline SnSe / NiSe / Ni prepared in Example 3 3 Se 2Hybrid nanorod array materials were analyzed by scanning electron microscopy. Figure 7 As shown, the prepared polycrystalline SnSe / NiSe / Ni 3 Se 2 The nanorod arrays grow uniformly and vertically on the nickel foam skeleton and there are gaps between the rods.

[0048] Example 4 Polycrystalline SnSe / NiSe / Ni 3 Se 2 Preparation of hybrid nanorod array materials

[0049] (1) While continuously feeding N 2 Under the atmosphere of 4 Completely dissolve in 3 mL of deionized water, then add 2 mmol of Se powder until it is reduced to a clear and transparent solution.

[0050] (2) Add 0.05 mmol of SnCl to the clear solution obtained in step (1) 2 ·2H 2 O and a mixed solution of 0.5mmoLNaOH (volume 1mL), 2mmoLNH 4 F solution (volume 25 mL) and an area of ​​1 × 4 cm 2 The nickel foam was then hydrothermally reacted at 180 °C for 6 h to finally obtain the polycrystalline SnSe / NiSe / Ni 3 Se 2 Hybrid nanorod array materials.

[0051] Example 5 Polycrystalline SnSe / NiSe / Ni 3 Se 2 Preparation of hybrid nanorod array materials

[0052] (1) While continuously feeding N 2 Under the atmosphere of 4 Completely dissolve in 3 mL of deionized water, then add 4 mmol Se powder until it is reduced to a clear and transparent solution.

[0053] (2) Add 0.05 mmol of SnCl to the clear solution obtained in step (1) 2 ·2H 2 O and a mixed solution of 0.5mmoLNaOH (volume 1mL), 2mmoLNH 4 F solution (volume 25 mL) and 2 × 4 cm 2 The nickel foam was then hydrothermally reacted at 180 °C for 6 h to finally obtain the polycrystalline SnSe / NiSe / Ni 3 Se 2Hybrid nanorod array materials.

[0054] Comparative Example 1 Rhombohedral NiSe / Ni 3 Se 2 Preparation

[0055] (1) While continuously feeding N 2 Under the atmosphere of 4 Completely dissolve in 3 mL of deionized water, then add 1 mmol of Se powder until it is reduced to a clear and transparent solution.

[0056] (2) Add 0.5 mmol NaOH solution (volume 1 mL), 1.5 mmol NH 4 F solution (volume 25 mL) and an area of ​​1 × 4 cm 2 The nickel foam was then hydrothermally reacted at 180 °C for 12 h to finally obtain the rhombohedral NiSe / Ni 3 Se 2 Hybrid nanorod array materials.

[0057] Rhombohedral NiSe / Ni prepared in Comparative Example 1 3 Se 2 The hybrid nanorod array material was analyzed by scanning electron microscopy and XRD. Figure 8 As shown in the scanning electron microscopy image, the prepared rhombohedral NiSe / Ni 3 Se 2 The hybrid nanorod arrays are grown on the nickel foam skeleton, and the morphology of the rods is relatively irregular. Fig. 9 Rhombohedral NiSe / Ni 3 Se 2 XRD pattern of hybrid nanorod array material, its characteristic peaks correspond to rhombohedral phase NiSe (standard card JCPDS18-0887) and rhombohedral phase Ni 3 Se 2 (Standard card JCPDS19-0841), indicating rhombohedral NiSe / Ni 3 Se 2 Successful preparation.

[0058] Example 6 Polycrystalline SnSe / NiSe / Ni 3 Se 2 Application of hybrid nanorod array materials as electrocatalysts in HER, UOR and UOR-assisted water electrolysis for hydrogen production

[0059] Using CHI 660E as the electrochemical workstation, the performance tests of HER, UOR and UOR-assisted water electrolysis for hydrogen production were carried out in 1.0 M KOH, 1.0 M KOH + 0.5 M urea and 1.0 M KOH + 0.5 M urea electrolytes, respectively.

[0060] For HER and UOR, the polycrystalline SnSe / NiSe / Ni grown on the nickel foam skeleton prepared in Example 1 was used. 3 Se 2 and rhombohedral NiSe / Ni 3 Se 2 (0.25cm×0.25cm) was used as the working electrode, the graphite rod electrode and the Hg / HgO electrode were used as the counter electrode and the reference electrode, respectively, and the linear sweep voltammetry (LSV) curves were obtained in the potential windows of -0.8~-1.5V (HER) and 0.1~0.7V (UOR), respectively. The LSV curves were compensated by iR to eliminate the influence of solution impedance.

[0061] For UOR-assisted water electrolysis to produce hydrogen, the polycrystalline SnSe / NiSe / Ni grown on the nickel foam skeleton prepared in Example 1 3 Se 2 They were used as cathode and anode for electrocatalytic tests, respectively.

[0062] Fig.10 a and Fig.10 b are polycrystalline SnSe / NiSe / Ni 3 Se 2 and rhombohedral NiSe / Ni 3 Se 2 HER and UORLSV polarization curves, from which it can be seen that compared with the rhombohedral phase NiSe / Ni 3 Se 2 Comparative sample, polycrystalline SnSe / NiSe / Ni 3 Se has a larger current density and a smaller voltage in both HER and UOR reactions, highlighting its superior HER and UOR catalytic activity. Tafel slope is an important parameter reflecting reaction kinetics. In order to further reveal the polycrystalline SnSe / NiSe / Ni 3 Se 2 and rhombohedral NiSe / Ni 3 Se 2 The speed of the related reaction kinetics and the associated Tafel slope are calculated.

[0063] like Fig.11 a and Fig.11 b shows the polycrystalline SnSe / NiSe / Ni 3The Tafel slopes of Se in HER and UOR reactions are 39 mV dec, respectively. -1 and 31mV dec -1 , which is significantly lower than that of rhombohedral NiSe / Ni 3 The Tafel slope of Se (the Tafel slope of HER is 82mV dec -1 The Tafel slope of UOR is 45mV dec -1 ), indicating that the polycrystalline SnSe / NiSe / Ni 3 Se 2 Faster HER and UOR reaction kinetics.

[0064] When NIR light is irradiated on SnSe / NiSe / Ni 3 Se 2 When the surface is exposed, its UOR performance is significantly improved. Fig.12 The UOR LSV polarization curves without NIR irradiation and at different NIR irradiation intensities are given. As the NIR irradiation intensity increases from NIR1 to NIR2, NIR3 and NIR4, the polycrystalline SnSe / NiSe / Ni 3 Se 2 The UOR catalytic performance is improved to the best, with 10, 500 and 1000 mA cm at only 1.28 V, 1.34 V and 1.37 V respectively. -2 , better than the performance without NIR irradiation.

[0065] In addition, under NIR4 irradiation, the polycrystalline SnSe / NiSe / Ni 3 Se 2 The SnSe / NiSe / Ni 3 Se 2 ||SnSe / NiSe / Ni 3 Se 2 The electrolyzer only needs 1.37V and 1.54V to drive 10 and 100mA cm -2 , which is much better than the performance without NIR irradiation (1.41V and 1.61V) (such as Fig.13 As shown in Figure 4, it is confirmed that the introduction of photothermal effect significantly improves the intrinsic catalytic activity of the catalyst. 3 Se 2 ||SnSe / NiSe / Ni 3 Se 2 The electrolyzer can be operated at 100 mA cm -2 The stable operation for 120 h at a current density of 1.5 % without obvious voltage decay proves the significant promoting effect of photothermal effect on stability (such as Fig.14shown).

[0066] In summary, the synthesis process of the present invention is simple, controllable, and the raw materials are abundant and easily available. 3 Se 2 The novel polycrystalline structure of the hybrid nanorod array material creates more high-energy active sites and synergistic catalytic centers, which in turn demonstrates excellent performance in the fields of electrocatalytic HER, UOR, and UOR-assisted water electrolysis to produce hydrogen. In particular, the photothermal effect introduced by NIR near-infrared light significantly improves the kinetics and thermodynamics of the UOR catalytic reaction, providing important support for the efficient operation of the catalytic reaction and showing broad commercial application potential.

[0067] The above is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any simple change or equivalent replacement of the technical solution that can be obviously obtained by any technician familiar with the technical field within the technical scope disclosed in the present invention falls within the protection scope of the present invention.

Claims

1. A method for preparing a polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorod array material, characterized in that: The following steps are involved: (1) Under a continuous N2 atmosphere, NaBH4 was completely dissolved in deionized water, and then Se powder was added until it was reduced to a clear and transparent solution; (2) Adding a mixed solution of SnCl2·2H2O and NaOH, a NH4F solution and nickel foam in sequence to the clear transparent solution in step (1), followed by a hydrothermal reaction, and finally obtaining polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorods in situ vertically grown on the nickel foam skeleton.

2. The method for preparing a polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorod array material according to claim 1, characterized in that: The amount of NaBH4 in step (1) is 1-6 mmol, the amount of Se powder is 1-4 mmol, and the volume of deionized water is 1-6 mL.

3. The method for preparing a polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorod array material according to claim 1, characterized in that: In step (2), the amount of SnCl2·2H2O is 0.05mmoL, the amount of NaOH is 0.5-1.5mmoL, the amount of NH4F is 1-2mmoL, the volume of the mixed solution of SnCl2·2H2O and NaOH is 1mL, and the volume of the NH4F solution is 25mL.

4. The method for preparing a polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorod array material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 120-200° C., and the reaction time is 4-12 hours.

5. The method for preparing a polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorod array material according to claim 1, characterized in that: The area of ​​the nickel foam described in step (2) ranges from 1×2 to 2×4 cm 2 .

6. A polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorod array material prepared by any one of the preparation methods of claims 1-5, consisting of orthorhombic SnSe, hexagonal NiSe and rhombohedral Ni3Se2, wherein: The diameter of SnSe / NiSe / Ni3Se2 hybrid nanorods is 100-300 nm.

7. Application of a polycrystalline SnSe / NiSe / Ni3Se2 hybrid nanorod array material as claimed in claim 6 as an electrocatalyst in urea oxidation reaction, hydrogen evolution reaction and hydrogen production by electrolysis of water assisted by urea oxidation reaction.

8. The use according to claim 7, characterized in that: When the urea oxidation reaction is used to assist the electrolysis of water to produce hydrogen, a SnSe / NiSe / Ni3Se2||SnSe / NiSe / Ni3Se2 electrolyzer is used to achieve a driving voltage of 10 mA cm at a voltage of 1.37 V and 1.54 V. -2 and 100mA cm -2 .

Citation Information

Patent Citations

  • Nickel selenide-trinickel diselenide nanorod composite material, and preparation method and application thereof

    CN113470983A

  • Nano-catalyst, preparation method and application of nano-catalyst in OER, UOR, HER and urea full water splitting reaction

    CN117512658A

  • Multi-core cobalt diselenide nanowire-porous carbon fiber composite material and preparation and application thereof

    CN118039897A